INTERAKSI KEKUASAAN, BUDAYA, DAN PEMBELAJARAN DALAM MEMBENTUK STRATEGI ORGANISASI - Handyman Manalu, Brilliant; Mustofa, Amirul; Yunus, Eddy (SIBATIK JOURNAL: Jurnal Ilmiah Bidang Sosial, Ekonomi, Budaya, Teknologi, Dan Pendidikan, 2025)
This study aims to examine the influence of the interaction between power, culture, and learning in the formulation of organizational strategy. Power within an organization, which is distributed across various levels, affects who can make strategic decisions and how these decisions are accepted and implemented. Organizational culture, encompassing values, norms, and customs, plays a crucial role in determining how strategies are developed and executed. Organizational learning, as a continuous process of acquiring knowledge and experience, allows organizations to adapt to market and technological changes. This research employs a descriptive qualitative approach, utilizing document analysis and relevant literature studies. The results indicate that these three elements interact and significantly influence the formation of organizational strategies. Organizations that can effectively manage power, culture, and learning have a greater chance of formulating and implementing successful, adaptive, and sustainable strategies. However, a lack of harmony among these elements may hinder the effectiveness of the strategies implemented. Therefore, it is crucial for organizational leaders to understand these internal dynamics and ensure that these three elements support each other in strategy formulation and execution.